Effect of the slope of the terrain and tertiary pipes in the uniformity of irrigation, humid bulb and pear crop yield (Pisum sativum) - Condori Valverde, Edgar (2024)
The Sierra of Perú region has agricultural soils with pronounced slopes that are not used throughout the year, because there are limitations when applying traditional gravity irrigation that leads to low infiltration speed, soil erosion, runoff formation, leaching, leaching of applied fertilizers and low irrigation efficiency; In that understanding, the objective of the investigation was to evaluate the effect of the slope of land and the arrangement of tertiary pipes on the uniformity of irrigation, wet bulb formation and the crop yield of peas. Three plots were conditioned with slopes of 10%, 20%and 40%; And in each plot three irrigation subunits were installed, inserting 0, 2 and 6 valves in the tertiary pipes, having a total of 09 treatments. The subunits were installed with irrigation tapes of 1.6 l/h of emitter flow at 20cm between drippers and 60cm between sides. The irrigation uniformity coefficient (CU) was determined with the Keller and Karmeli method; Treatment 7 (slope of land 40% + tertiary pipe with 06 valves) presented greater efficiency Cu = 96.30%; valued with an excellent qualifier to irrigation uniformity. All treatments have similarity in the formation of the humid bulb at 45min of irrigation; With a wet soil radius ≥10cm, depth ≥30cm on sandy frank soil. Regarding performance, treatment 3 (slope of land 10% + tertiary pipe with 02 valves) presented 10.75 t/ha.